Understanding The Limitations Of Human Rights In Indonesia - Arief Fahmi Lubis (International Journal of Law and Society, 2024)
Every individual bears the responsibility of honoring the rights of others within the context of national and state life. This research aims to illustrate that while exercising their rights and freedoms, individuals are obligated to adhere to legal constraints. This adherence is intended to ensure the acknowledgment and respect for the rights and freedoms of others, as well as to fulfill equitable demands in alignment with moral considerations, security imperatives, and the maintenance of public order within a democratic society. This study employs a qualitative research method with a descriptive approach. The systematic, factual, and timely data collection is conducted following the research framework and objectives. The findings suggest that the current conceptualization of limitations on human rights may evolve in the future. The crucial question now pertains to how advocates for a shift in thought construction can effectively leverage the constitutional mechanisms available to them.